A Retrospective Analysis of the Treatment of Melasma Using a Fractional Long-Pulsed Alexandrite Laser in Korean Patients. Issue 8 (August 2016) - Lee, Min Kyung; Min, Kyung Sik; Park, Eun Joo; Kim, Kwang Ho; Kim, Kwang Joong
Abstract : BACKGROUND: Long-pulsed, 755-nm, alexandrite lasers have been shown to be effective and safe in the treatment of pigmentary lesions. OBJECTIVE: Clinical outcomes and side effects in the treatment of melasma using a fractional, long-pulsed, alexandrite laser were assessed. MATERIALS AND METHODS: Forty-eight patients with melasma received 2 to 4 treatment sessions of fractional, long-pulsed, alexandrite laser at 2 to 3 weeks intervals. The parameter of treatment was 60 to 80 J/cm 2 without dynamic cooling device using 15-mm spot size of fractional hand piece, with a 0.5- to 1-millisecond pulse width. RESULTS: The mean modified melasma area and severity index score decreased significantly 2 months after the final treatment compared with baseline (16.5 ± 8.2 vs 11.5 ± 7.0; p = .002). The patients with epidermal type melasma were more effective compared to dermal type ( p < .001). CONCLUSION: Long-pulsed alexandrite lasers using a fractional hand piece are moderately effective in the treatment of melasma with low risk of adverse effects, and it is suggested that fractional, long-pulsed, alexandrite laser with combination of other modalities can be an additional therapeutic option in patients with melasma.